2019
DOI: 10.3390/bios9040139
|View full text |Cite
|
Sign up to set email alerts
|

Biochar from Brewers’ Spent Grain: A Green and Low-Cost Smart Material to Modify Screen-Printed Electrodes

Abstract: In the present study, biochar from brewers’ spent grain was used, for the first time, to develop screen-printed electrodes. After having investigated the dispersion behaviour of biochar in different organic solvents, a biochar-based screen-printed electrode was prepared with the drop-casting technique. In order to understand the electrochemical potentiality and performances of the biochar/sensor tool, different electroactive species, i.e., ferricyanide, benzoquinone, epinephrine, ascorbic, and uric acids, were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 37 publications
0
30
0
Order By: Relevance
“…Trials showed that tested additions were effective and allowed for the production of a biodegradable counterpart for expanded polystyrene trays [ 115 ]. Moreover, BSG has been mentioned as a sustainable material that could be used for the manufacturing of electrodes [ 116 ].…”
Section: Sustainable Materialsmentioning
confidence: 99%
“…Trials showed that tested additions were effective and allowed for the production of a biodegradable counterpart for expanded polystyrene trays [ 115 ]. Moreover, BSG has been mentioned as a sustainable material that could be used for the manufacturing of electrodes [ 116 ].…”
Section: Sustainable Materialsmentioning
confidence: 99%
“…In particular, the antioxidant, anti-atherogenic, anti-inflammatory, and anti-carcinogenic activities of chemical compounds in BSG have been considered (Ikram et al 2017 ; Lynch et al 2016 ; McCarthy et al 2013 ). Finally, methods for exploitation of BSG in terms of food and energy production, and in the chemical and agronomic sectors have been reviewed (Cancelliere et al 2019 ; Mussatto 2014 ; Xiros and Christakopoulos 2012 ; Aliyu and Bala 2011 ; Mussatto et al 2006 ). In this context, the aim of this mini-review is to present the current literature on BSG from a microbiological point of view.…”
Section: Introductionmentioning
confidence: 99%
“…Biological activity of these residues makes long term storage difficult. The literature reports ongoing work on various new ways of using BSG, including extraction of polyphenols [10,11], other anti-oxidants [12,13], functional cardioprotective lipids for pharmaceutic use [14], proteins [15], fodder for edible insects [16], material for disposable trays [17], natural rubber modifier [18], as well as feedstock for production of pigments [19] and biochar, for subsequent use as soil amendment [20] or sustainable material for electrodes [21].The potential use of this residue as a fuel has been suggested by several authors so far [7][8][9]22,23]. The relatively high initial moisture content of spent grain makes hydrothermal valorization techniques the most sensible choice [8,9].…”
mentioning
confidence: 99%